ANALISIS PERBEDAAN HARGA JUAL PAKAIAN WANITA ANTARA PASAR TRADISIONAL DAN PASAR MODERN DI KOTA MOJOKERTO - Rahanita Rahanita; Muhammad Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2018)
This research aims to determine the differences in selling prices and the factors that influence the price of women's clothing line between traditional markets and modern markets. This research is a qualitative research. The samples are determined based on nonprobability sampling method of 15 women's clothing merchants in Benteng Pancasila Market and 15 garment traders in Sunrise Mall. The analytical technique used is independent sample t-test by using computer program SPSS version 21. The results of this study indicate that the price of women's clothing in the Benteng Pancasila Market is lower than in Sunrise Mall.Keywords: Traders of Women Clothing, Sample T-Test and Selling Price.